UNKNOWN HISTORY: LE CORBUSIER IN FRONT OF THE ‘ACADEMISM’ OF JAN DE RANITZ IN THE PREPARATIONS FOR THE NEW UNITED NATIONS HEADQUARTERS AT NEW YORK (1946) / Una historia desconocida: Le Corbusier frente al “Academicismo” de Jan De Ranitz (...) - Molema, Jan (Proyecto, Progreso, Arquitectura, 2013)
SUMMARY Soon after the second world war the general assembly of the United Nations decreed that the seat of the organization were to be located in the United States of America. A search commission started a research of the possibilities in this country. The commission amongst others counted three experts: the Frenchman Le Corbusier, the Soviet–Russian Bassov and the Dutchman Jan de Ranitz. Le Corbusier worried about the composition of the commission: “I am obliged to inform you about the characteristic distressing situation here in NY in the commission for the Headquarters of the UN created by one of the members of the commission, that I am part of: the Jenkheer de Ramitz (sic!), who graduated from the university of Delft and tries to get a position from which he may drag down everything into the darkest academic catastrophe.” In this article I will explain what happened in New York in 1946. A fight between big ‘frames of mind’, incapable to butch an inch where it came to principles of town planning. RESUMEN Poco después de la Segunda Guerra Mundial, la Asamblea General de las Naciones Unidas decretó que la sede de la organización debía estar ubicada en los Estados Unidos de América. Una comisión para la búsqueda de un emplazamiento comenzó a investigar las posibilidades de este país. La comisión contó, entre otros, con tres expertos: el francés Le Corbusier, el soviético-ruso Bassov y el neerlandés Jan de Ranitz. Le Corbusier estaba preocupado por la composición de la comisión: “Me veo en la obligación de informarle sobre la angustiosa situación creada aquí en Nueva York en la comisión para la Sede de las Naciones Unidas, provocada por uno de los miembros de la comisión, y de la que yo formo parte: Jenkheer de Ramitz (¡sic!), quien se graduó de la Universidad de Delft y que trata de conseguir una posición desde la que puede arrastrar a todos a la más oscura catástrofe académica”. En este artículo voy a explicar lo que sucedió en Nueva York en 1946. Una lucha entre grandes “estados de ánimo”, incapaces de ceder una pulgada en el campo de los principios urbanísticos.